Deferasirox for transfusion‐dependent patients with myelodysplastic syndromes: safety, efficacy, and beyond (GIMEMA MDS0306 Trial). (10th April 2014) - Angelucci, Emanuele; Santini, Valeria; Di Tucci, Anna Angela; Quaresmini, Giulia; Finelli, Carlo; Volpe, Antonio; Quarta, Giovanni; Rivellini, Flavia; Sanpaolo, Grazia; Cilloni, Daniela; Salvi, Flavia; Caocci, Giovanni; et al.
Abstract Background In the absence of randomized, controlled trial data to support iron chelation therapy in transfusion‐dependent patients with myelodysplastic syndromes (MDS), continued evidence from large prospective clinical trials evaluating the efficacy and safety of iron chelation therapy in this patient population is warranted. Methods The safety and efficacy of deferasirox was examined in a prospective, open‐label, single‐arm, multicenter trial of transfusion‐dependent patients with International Prognostic Scoring System low‐ or intermediate‐1‐risk MDS and evidence of transfusion‐related iron overload. The effects of deferasirox therapy on hematological response and disease progression were also examined. Results Of 159 participants enrolled from 37 Italian centers, 152 received ≥1 dose of deferasirox (initiated at 10–20 mg/kg/day and titrated as appropriate), and 68 completed the study. Of 84 patients who discontinued deferasirox therapy, 22 died during the trial, and 28 withdrew due to an adverse event (AE). Fourteen treatment‐related grade 3 AEs occurred in 11 patients, whereas no grade 4 or 5 drug‐related AEs were reported. Significant risks for dropout were a higher serum ferritin level at baseline, a higher MDS‐Specific Comorbidity Index, and a shorter diagnosis–enrollment interval. Median serum ferritin level fell from 1966 ng/mL to 1475 ng/mL (P < 0.0001). The cumulative incidence of transfusion independence, adjusted for death and disease progression, was 2.6%, 12.3%, and 15.5% after 6, 9, and 12 months, respectively. Conclusions Deferasirox therapy in transfusion‐dependent patients with MDS was moderately well tolerated and effectively lowered serum ferritin levels. Positive hematological responses were observed, and a subset of patients achieved transfusion independence.